Information systems strategic management : an integrated approach - Clarke, Steve, 1950- (London ; New York : Routledge, 2001)
A comprehensive guide to the strategic management of information systems within business and public sector organisations. Key issues covered include: corporate strategy, information systems strategy and the technical versus social debate.
Includes bibliographical references and index.
oif 16/10/14
Loan
Keywords: Strategic planning; Management information systems; Management information systems -- Case studies; Strategic planning -- Case studies